Pemberdayaan Ibu Rumah Tangga Melalui Pemanfaatan Lahan Pekarangan Di Desa Midang Kecamatan Gunungsari Kabupaten Lombok Barat - Sri Maryati; Sri Supartiningsih; Wuryantoro; I Ketut Budastra; Taslim Sjah (Jurnal SIAR ILMUWAN TANI, 2020)
The availability of agricultural land resources was getting smaller every year due to changing land functions. Therefore, it was necessary to optimize the use of land resources, namely one of the ways by utilizing yard land that can be done by housewives who are used to grow various horticultural crops. This activity was also in line with the government's program to develop Sustainable Food House Areas (KRPL). The aim of the activity in general was to motivate the community (especially housewives) to be able to use their yards to plant horticultural crops. The location of community service activities was Midang Village, Gunungsari District, West Lombok Regency. The method used is the method of lectures and discussions as well as nursery practices. Lectures use LCD tools, loudspeakers (mike) and also distribution of copies of material summaries so that participants can easily understand them. Participants in the activity were Midang Village PKK cadres. The results of the activity were considered very positive to increase participants' knowledge and participants were motivated by enthusiastic discussion. The evaluation results show that extension activities were very useful in increasing community knowledge, and activities can be carried out again in the same location as the continuation of previous activities, such as making fertilizer from household waste or in different locations with the same theme